The use of Digital Technologies in the Activities of Insurance Companies - Akmalovna, Zakirkhodjayeva Shirin (Academic Journal of Digital Economics and Stability, 2022)
The relevance of the study is related to the accelerated pace of automation and digitalization of the economy, which open up new opportunities to increase the efficiency of insurance market participants. Such a process will allow reducing costs and increasing income in insurance organizations. The purpose of the work is to determine the current trends of digitalization penetration into the insurance market. The subject of the study is the processes of digitalization and consolidation of the insurance market. The analysis of the peculiarities of the insurance market development in the conditions of digitalization is carried out and the prospects for further development are indicated. Over the past year, there has been an increase in the intensity of the development of Internet communication between companies and customers in the insurance market. There is an appearance of new insurance products, which is associated with the ability to collect more data about customers of insurance companies. The results obtained can be used to substantiate the ways of development of individual insurance companies, and the study may be of interest to practitioners.